Global research trends on the links between the gut microbiota and diabetes between 2001 and 2021: A bibliometrics and visualized study - Zhang, Boxun; Jin, Zishan; Zhai, Tiangang; Ding, Qiyou; Yang, Haoyu; Wang, Jia; Zhang, Lili; Zhao, Linhua (Frontiers in Microbiology, 2022)
Background: Over the past 20 years, evidence has suggested that gut microbiota plays an important role in metabolic homeostasis. The relationship between gut microbiota and diabetes has become the focus of considerable scientific interest. With the sharp increase in publications in this area, it is imperative to analyse the relevant articles using bibliometrics methods. Methods: Publications on "the gut microbiota and diabetes" were retrieved and downloaded from the Web of Science Core Collection database. Microsoft Excel 2020, VOSviewer, CiteSpace 5.8.R3 and Co-Occurrence 9.94 software were used for data analysis and visualisation. Country/academic institution, journal, author, subject category, keyword and reference were analyzed thoroughly. The cutting-edge directions in this field were also determined by analyzing keywords and key articles. Results: A total of 2342 documents were included in the analysis; the number of articles in this field has increased yearly, particularly after 2010. China and the University of Copenhagen are the country and research institution associated with the largest number of publications. Nutrients have published 191 articles in this field, ranking first among highly productive journals in the number of publications. The researcher Cani PD affiliated with the University of Leuven, Belgium, published the greatest number of articles in this field between 2001 and 2021 and was also ranked as the first co-cited author and the largest contributor of highly cited papers in this field. Endocrinology & Metabolism was the most common subject category. Three of the most frequently found keywords, besides terms related to "microbiota" and "diabetes", were "obesity", "probiotics", and "inflammation". Akkermansia muciniphila, Faecalibacterium prausnitzii, trimethylamine n-oxide and branched-chain amino acids are intestinal bacteria or metabolites that have attracted more attention in recent years. Natural products represented by Chinese herbal medicine and some protein receptors or signalling pathways such as aryl hydrocarbon receptor, farnesoid X receptor and AMP-activated protein kinase were frontiers in this field. Conclusion: the rapid development of research on the gut microbiota has deepened the understanding of the physiology and pathology of diabetes, providing new insights into different approaches to treatment. In the future, further interdisciplinary innovation, clinical transformation, and application may receive more attention.